Nasal steroids, irrigation, oral antibiotics, and subgroup targeting for effective management of acute sinusitis (NOSES): Protocol for a comparative effectiveness randomized controlled trial - Daniel Merenstein; Nawar Shara; David P. Rabago; Derjung Mimi Tarn; Bruce Barrett; Alex H. Krist; Sebastian T. Tong; Aleksandra E. Zgierska; Tina P. Tan; Keisha Herbin Smith; Gabriela Villalobos; Charles R. Fencil; et al. (PLoS ONE, 2026)
Introduction Acute rhinosinusitis (ARS) affects approximately 15% of adults annually. It accounts for nearly 30 million outpatient visits and one in five antibiotic prescriptions, and contributes to over $11 billion in direct healthcare costs in the United States. Because routine clinical evaluation cannot reliably distinguish viral from bacterial ARS, antibiotics are frequently prescribed for infections that are likely viral. Non-antibiotic therapies such as intranasal corticosteroids (INCS) and saline nasal irrigation may provide symptom relief, but their comparative effectiveness in ARS has not been rigorously evaluated. Objectives This protocol describes the design and methodology of a large, multi-center, pragmatic randomized controlled trial to evaluate antibiotic and non-antibiotic treatment strategies for ARS. The trial will compare supportive care, and clinical and laboratory indicators that may identify subgroups most likely to benefit from specific therapies. Methods This placebo-controlled trial is underway in primary care and urgent care settings in six regions across the U.S. Adults aged 18–75 years with ARS initially receive clinician-directed care. Participants who do not improve after 9 days of symptoms will be randomized into one of four groups: antibiotics alone; placebo-antibiotics plus INCS; antibiotics plus INCS; or placebo-antibiotics alone. All participants receive educational materials and kits for saline nasal irrigation. The trial will enroll 3,720 participants, with approximately 60% expected to enter the randomized phase. Primary outcomes include symptom severity prior to and 3 days post-randomization, as measured by the modified Sino-Nasal Outcome Test-16). Significance This trial will generate high-quality evidence to inform targeted treatment of ARS, identify subgroups most likely to benefit from antibiotics or non-antibiotic therapies, and support more judicious antibiotic stewardship in routine clinical practice.